Prospective study on breastfeeding, lipid profile and cardiovascular risk markers in women with familial hypercholesterolaemia: study protocol for the FH-FEMINA study - Klevmoen, Marianne; Mulder, Janneke W C M; Bogsrud, Martin P; Retterstøl, Kjetil; Vesterbekkmo, Elisabeth K; Pedersen, Eva K R; Freiberger, Tomas; Vrablik, Michal; Vaclova, Martina; Hovland, Anders; Vethe, Nils Tore; Brekke, Hilde Kristin; et al. (BMJ open, 2025)
INTRODUCTION: Early and lifelong treatment is essential in patients with familial hypercholesterolaemia (FH) due to genetically elevated low-density lipoprotein cholesterol (LDL-C) from the first years of life. In women with FH, lipid-lowering treatment is interrupted during childbearing years due to contraindication of the medication during conception, pregnancy and breastfeeding. However, little is known about the impact of breastfeeding on lipid profile and other risk markers for atherosclerotic cardiovascular disease (ASCVD) in women with FH compared with women without hypercholesterolaemia, and to what extent statins transfer into breast milk.We aim to investigate (1) the association between breastfeeding and serum lipid profile in women with and without FH; (2) the association between breastfeeding and other ASCVD risk markers in women with and without FH and (3) the concentration of statins in breast milk of women with FH. METHODS AND ANALYSIS: FH-FEMINA is a prospective study aiming to include 50 women with FH in Norway, the Netherlands and the Czech Republic. Additionally, 20 women without hypercholesterolaemia will be enrolled as a control group in Norway. Women will be included at the first study visit in gestational week 36, and follow-up visits will be scheduled at 2-4 weeks, and at 3, 6, 9 and 12 months postpartum. Information on lifestyle factors, treatment history and current and previous pregnancies will be collected. At each visit, a non-fasting blood sample, breast milk sample and information on diet, body mass index and blood pressure will be collected. Additional blood samples will be collected from the women with FH at 2, 4, 5, 7, 8, 10 and 11 months postpartum for as long as they are breastfeeding. At (re-)initiation of statin treatment, breast milk samples from women with FH will be collected for drug concentration measurements. ETHICS AND DISSEMINATION: Ethical approval will be obtained prior to study start in all three countries. Participants will be informed about the study and receive ample time to ask questions before the informed consent form is signed. The findings from this study will be disseminated to healthcare professionals, researchers and patients via peer-reviewed scientific article(s), conferences, patient organisations and social media. TRIAL REGISTRATION NUMBER: NCT05367310.
Keywords: kojení; statiny; hyperlipoproteinemie typ II; kardiovaskulární nemoci; Humans; Primary Prevention; Netherlands; rizikové faktory kardiovaskulárních chorob; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Nizozemsko; mateřské mléko; Female; dospělí; lipidy; lidé; Biomarkers; Norway; Hyperlipoproteinemia Type II; Postpartum Women; Adult; Coronary heart disease; ženské pohlaví; biologické markery; Milk, Human; Cardiovascular Diseases; Heart Disease Risk Factors; Czech Republic; Lipids; Maternal medicine; Breast Feeding; Česká republika; prospektivní studie; Cardiovascular Disease; Norsko; Prospective Studies